2021
DOI: 10.1093/mollus/eyab013
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphological evidence for a unified, inclusiveSinotaia quadrata(Caenogastropoda: Viviparidae: Bellamyinae)

Abstract: The taxonomy of species in the caenogastropod genus Sinotaia (Viviparidae: Bellamyinae) has been a complex and controversial issue since the 19th century. Sinotaia quadrata, the type species of Sinotaia, comprises many named forms and transitions between them, and the taxonomic validity of some species similar to S. quadrata also requires clarification. To clarify relationships in this common and significant member of the freshwater benthos, we reconstructed a phylogeny for species related to S. quadrata based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In this study, SMRT sequencing of full-length 16S rRNA genes was used to compare the gut microbiota of three species of wild herbivorous snails living in the same freshwater environment. Although three snail species, namely Sinotaia quadrata (SQ), Boreoelona ussuriensis (BU) and Radix plicatula (RP), are common in China (Wu et al, 2017;Ye et al, 2021); however, their intestinal microbial communities have not yet been reported. Through the successful identification of a number of bacteria up to the species level, this work yielded distinct gut microbial community profiles for the three snail species.…”
Section: Diversity Of the Intestinal Bacterial Communities Of Freshwa...mentioning
confidence: 99%
“…In this study, SMRT sequencing of full-length 16S rRNA genes was used to compare the gut microbiota of three species of wild herbivorous snails living in the same freshwater environment. Although three snail species, namely Sinotaia quadrata (SQ), Boreoelona ussuriensis (BU) and Radix plicatula (RP), are common in China (Wu et al, 2017;Ye et al, 2021); however, their intestinal microbial communities have not yet been reported. Through the successful identification of a number of bacteria up to the species level, this work yielded distinct gut microbial community profiles for the three snail species.…”
Section: Diversity Of the Intestinal Bacterial Communities Of Freshwa...mentioning
confidence: 99%
“…Bellamya aeruginosa (Gastropoda: Probranchia), is a widespread viviparid freshwater snail species that is distributed across East Asia (Qiu et al, 2017). It is also invasive in other regions, such as Europe and South America (Ye et al, 2021). Because of its delicious meat and high nutritional value, B. aeruginosa has been consumed as a delicacy and medicinal food since ancient times (Mak Sau-Wa, 2022).…”
Section: Introductionmentioning
confidence: 99%